Combination of rheumatoid arthritis and sarcoidosis, which had occurred during rituximab therapy, complicated secondary immunodeficiency and intolerance to the main basic drugs: Case repost and literature review - O. A. Golovina; N. V. Demidova; A. V. Alekseeva (Научно-практическая ревматология)
Sarcoidosis is a rare multisystem disease which may accompany various autoimmune diseases in 17,6% cases. Despite of the fact that T-cell immunity impairments play a key role in these two conditions, their combination is extremely rare. It is difficult to choose therapy for patients with coexisted diseases, and it is even harder in case of comorbid pathology. In this article we considered a complicated case of treatment patient with a coexistence of rheumatoid arthritis and sarcoidosis, which had occurred during rituximab therapy. In addition to the combination of two autoimmune diseases, the selection of therapy for this patient was complicated by secondary immunodeficiency and intolerance to the main basic drugs.